Role of Gut Inflammation in Altering the Monocyte Compartment and Its Osteoclastogenic Potential in HLA–B27–Transgenic Rats. Issue 9 (8th August 2017) - Ansalone, Cecilia; Utriainen, Lotta; Milling, Simon; Goodyear, Carl S.
Abstract : Objective: To investigate the relationship between intestinal inflammation and the central and peripheral innate immune system in the pathogenesis of HLA–B27–associated spondyloarthritis using an HLA–B27–transgenic (B27‐Tg) rat model. Methods: The myeloid compartment of the blood and bone marrow (BM) of B27‐Tg rats, as well as HLA–B7–Tg and non‐Tg rats as controls, was evaluated by flow cytometry. Plasma from rats was assessed by enzyme‐linked immunosorbent assay for levels of CCL2 and interleukin‐1α (IL‐1α). Rats were treated with antibiotics for 4 weeks, and the myeloid compartment of the blood and BM was evaluated by flow cytometry. The osteoclastogenic potential of BM‐derived cells from antibiotic‐treated rats, in the presence or absence of tumor necrosis factor (TNF), was evaluated in vitro. Results: B27‐Tg rats had substantially higher numbers of circulating Lin−CD172a+CD43 low monocytes as compared to control animals, and this was significantly correlated with higher levels of plasma CCL2. Antibiotic treatment of B27‐Tg rats markedly reduced the severity of ileitis, plasma levels of CCL2 and IL‐1α, and number of BM and blood Lin−CD172a+CD43 low monocytes, a cell subset shown in the present study to have the greatest in vitro osteoclastogenic potential. Antibiotic treatment also prevented the TNF‐dependent enhancement of osteoclastogenesis in B27‐Tg rats. Conclusion: Microbiota‐dependent intestinal inflammation in B27‐Tg rats directly drives the systemic inflammatory and bone‐erosive potential of the monocyte compartment.